Intermittent Explosive Disorder in Male Juvenile Delinquents in China - Shao, Yang; Qiao, Yi; Xie, Bin; Zhou, Min (Frontiers in Psychiatry, 2019)
Objective: Although several previous studies have focused on the mental health problems in detained juvenile offenders in China and found high levels of major psychiatric morbidity, the prevalence of Intermittent explosive disorder (IED) in this group is still unknown. The purpose of this study is to discover the prevalence of IED among juvenile offenders in China as well as the difference in demographic characteristics and personality traits between IED offenders and the general population. Method: A total of 280 delinquent boys (Mean age 16.10 years) were interviewed by trained psychiatrists. The interview procedure included the recording of sociodemographic characteristics, criminal records, Composite International Diagnostic Interviews (CIDI), State-Trait Anger and Expression of Anger Inventory-2 (STAXI-2), and Modified Overt Aggression Scales (MOAS). Results: Of the 280 delinquent boys, 32 (11.4%) were diagnosed with IED, 129 (46.1%) were non-IED psychopathology controls (PC), and 119 (42.5%) were healthy controls (HC). Except for substance use disorder, no differences in psychiatric comorbidity were found between youth with IED and those with another psychiatric disorder. Compared with the PC and HC groups, those in the IED group were more likely to commit a violent crime such as rape, assault, and affray but less likely to explain their motive as money or property. The IED group also had a higher rate of recidivism history than the HC group. The IED group displayed higher levels of state and trait anger and anger expression than the HC group and lower levels of anger control than both the PC and HC groups. MOAS also showed that those in the IED group were more aggressive than those in the PC and HC groups. Conclusion: The relationships between IED with anger and aggression reflect the need to develop and implement specific and individually tailored intervention approaches to correct IED juvenile offenders’ behavior in order to prevent new crime.